Low-temperature growth of polycrystalline si thin film using RF magnetron sputtering / Shaiful Bakhtiar Hashim - Hashim, Shaiful Bakhtiar (2014)
A study on the growth of polycrystalline Silicon (poly-Si) on a glass Substrate at low temperature is being studied. The preparation was done by using direct deposition of Radiofrequency (RF) magnetron sputtering method. The physical and crystallinity of thin films was studied and investigated to focus on various deposition parameters such as RF power of 100 W to 300 W, deposition temperature of room temperature to 200 °C, sputtering pressure of 5 mTorr to 8 mTorr, argon gas flow rate of 40 sccm to 100 sccm and also the influence of Substrate bias power of +10 W to +150 W. The physical structures of the thin films were observed by using field emission scanning electron microscope (FESEM), JOEL JSM 7600F, atomic force microscope (AFM) XE-100 Park System AFM and Surface Profiler (SP, KLA Tencor P-6). The crystallinity of the thin films was observed by Raman spectroscopy (Horiba Jobin Yvon). Through the investigation, we found that even giving higher RF power, the thin films Start to crystallize but poly-Si thin films still not achieved. To overcome this problem, we explored the role of Substrate bias to fiirther enhance the crystallization of the thin films. The Substrate bias may provide higher energy during the bombardment and at the same time modifies the arrangement of particles to produce high crystalline quality. The results of the thickness and deposition rate measurements show that Substrate bias has influence on the growth of films on the Substrate. As the Substrate bias increase the deposition rate also increases due to the number of atom collision at the target which iead increasing the particles on the Substrate. From Raman spectroscopy result it showed that the Si-Si transverse optical (TO) peak was around 518 cm"1 for sample deposited at +30 W which indicates the existence of poly-Si phase. It shows that the thin film crystallized even at room temperature deposition with the influenced of the Substrate bias.